2013
DOI: 10.3342/ceo.2013.6.3.117
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in Head and Neck Cancer Patients: Pretreatment Evaluation, Predictive Factors, and Assessment during Radio-Chemotherapy, Recommendations

Abstract: Progress in head and neck cancer (HNC) therapies has improved tumor response, loco-regional control, and survival. However, treatment intensification also increases early and late toxicities. Dysphagia is an underestimated symptom in HNC patients. Impairment of swallowing process could cause malnutrition, dehydration, aspiration, and pneumonia. A comprehensive literature review finalized in May 2012 included searches of electronic databases (Medline, Embase, and CAB abstracts) and scientific societies meetings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 66 publications
2
120
0
10
Order By: Relevance
“…Treatment for head and neck cancer, particularly chemoradiotherapy, has been found to cause dysphagia or increase the severity of an existing swallowing impairment . A recent systematic review reported the incidence of dysphagia was 22% to 62% posttreatment . A further recent study has shown that patients with aspiration are also more likely to have had significant weight loss or a lower body mass index (BMI) …”
Section: Introductionmentioning
confidence: 99%
“…Treatment for head and neck cancer, particularly chemoradiotherapy, has been found to cause dysphagia or increase the severity of an existing swallowing impairment . A recent systematic review reported the incidence of dysphagia was 22% to 62% posttreatment . A further recent study has shown that patients with aspiration are also more likely to have had significant weight loss or a lower body mass index (BMI) …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in patients with neurodegenerative conditions, dementia and in very elderly patients, the presence of dysphagia and malnutrition could be both cause and consequence of functional decline, in a cycle in which dysphagia causes malnutrition, malnutrition contributes to functional decline, and functional decline aggravates dysphagia symptoms 8,13 . Dysphagia's most important complication is aspiration pneumonia [14][15][16] , which is responsible for 20% to 65% of deaths in head and neck cancer patients 17 , and is the most important cause of mortality in patients with neurodegenerative diseases 18 . Recent studies suggest that in very elderly patients deglutition rehabilitation could provide an improvement in nutritional status as well as a decrease in the incidence of pneumonia 19 .…”
Section: Introductionmentioning
confidence: 99%
“…1,3,[32][33][34]37 Nonetheless, weight loss has not been properly considered during HN treatment plans. It is important that clinicians are capable to recognize patients at risk for critical weight loss with the goal of providing the proper supportive care.…”
Section: Weight Loss and Rt Planningmentioning
confidence: 98%